Resistant identities: culture and politics among Kuwaiti youth. Issue 3 (2nd October 2017) - Buscemi, Emanuela
ABSTRACT: The present paper investigates the role of youth in contemporary Kuwait, and how their diverse resistance strategies contest and challenge dominant cultural and political paradigms, affecting identity construction and social patterns. It examines the distance between the government and youth, and a growing crisis of representation through the analysis of three main areas of resistant practices enacted by youth, seemingly interdependent and possibly overlapping: political mobilisation, political radicalisation and civic engagement. Political mobilisation concerns the protests staged in Kuwait mainly in 2012; political radicalisation examines political violence and terrorist episodes, while civic engagement investigates examples from an invigorated civil society. The article investigates and addresses youth practices employing classic and alternative social movements literature developed in Latin America and the Middle East, together with original ethnographic data.